2018
DOI: 10.3390/ijms19071946
|View full text |Cite
|
Sign up to set email alerts
|

Red (635 nm), Near-Infrared (808 nm) and Violet-Blue (405 nm) Photobiomodulation Potentiality on Human Osteoblasts and Mesenchymal Stromal Cells: A Morphological and Molecular In Vitro Study

Abstract: Photobiomodulation (PBM) has been used for bone regenerative purposes in different fields of medicine and dentistry, but contradictory results demand a skeptical look for its potential benefits. This in vitro study compared PBM potentiality by red (635 ± 5 nm) or near-infrared (NIR, 808 ± 10 nm) diode lasers and violet-blue (405 ± 5 nm) light-emitting diode operating in a continuous wave with a 0.4 J/cm2 energy density, on human osteoblast and mesenchymal stromal cell (hMSC) viability, proliferation, adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 87 publications
3
61
0
1
Order By: Relevance
“…Between Groups 2 (BM + HFB) and 3 (BM + HFB + PBMT), there was a statistical difference in relation to bone percentage in both periods, relating findings compatible with the literature when observing higher bone density [61,65], blood vessels, Havers canal development, maturation and organization of bone tissue, following the principles that the tissue will only respond to biostimulation if the energy is adequate, reaching the minimum limit, and when the energy is excessive, there may be tissue inhibition [22,66].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Between Groups 2 (BM + HFB) and 3 (BM + HFB + PBMT), there was a statistical difference in relation to bone percentage in both periods, relating findings compatible with the literature when observing higher bone density [61,65], blood vessels, Havers canal development, maturation and organization of bone tissue, following the principles that the tissue will only respond to biostimulation if the energy is adequate, reaching the minimum limit, and when the energy is excessive, there may be tissue inhibition [22,66].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it increases the adenosine triphosphate (ATP) and cellular mitotic activity [20]. Defined as the application of energy directly from noncoherent (light emitting diode) or coherent (lasers) light, with varying wavelengths between 405 and 1100 nm, it is capable of producing photochemical effects by modulating cells [21,22]. This new technology is the current focus of studies of the scientific community for presenting reparative mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…41 Also, molecular analyses indicated that red photobiomodulaton therapy in osteoblasts and hMSCs stem cells increased vinculin-rich clusters, osteogenic markers expression (Runx-2, alkaline phosphatase, osteopontin, Col I, OCN, DSPP, DMP1, and HSP27), and mineralized bone-like nodule structure deposition. [42][43][44] Adipogenic differentiation was previously investigated to characterize the stem cells or evaluate some materials. 18,25,30 However, until this moment, it was not used to quantify the lipid vesicle deposition induced by PBM.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that melanopsins, the non-visual pigments most sensitive to the blue range of visible spectrum, are located not only in the retina, but also in the cells of the skin and vascular wall [4]. It was proven that blue light phototherapy not only modulates circadian rhythms and affects the skin [3], but also can accelerate bone regeneration processes [16] and modulate the vascular tone [15]. The vasodilating effects can be a result of direct effect on the contractile elements of vascular smooth muscle cells [2] and also can be mediated by the release of the major endothelial vasodilator NO [4].…”
Section: Introductionmentioning
confidence: 99%